The world of learning 1994 (Bedford Square, London, 1994)
The book contains directory details for over 26,000 universities, colleges, schools of art and music, libraries, archives, learned societies, research institutes, museums and art galleries - arranged alphabetically by country
Keywords: universities and colleges - catalogs